Investigation of Epidemiology and Pathogenesis of Co-infection with Multiple Carbapenem-Resistant Enterobactereciae in Hospitalized Patients. (4th October 2017) - Holowka, Thomas; Monteforte, Melinda; Go, Roderick; Maramara, Bennadette; Khoo, Teresa; Chow, Robert; Abul, Yasin; Mahapatra, Rahul; Morgan, Alexa; Diago-Navarro, Elizabeth; Fries, Bettina C
Abstract: Background: Carbapenem-resistant Enterobactereciae (CRE) are an emerging cause of major morbidity and mortality in hospitalized patients. These organisms are difficult to treat due to antibiotic resistance conferred by plasmid-derived genes, most commonly bla KPC-2 and bla KPC-3 . In this study, patients infected with multiple distinct CRE species were investigated in order to better understand the epidemiology and pathogenesis of CRE co-infection. Methods: A retrospective study was undertaken using data from the CRaCKLe 2 study at Stony Brook University Hospital between July 2016 and April 2017. Medical records of patients infected with multiple CRE species were reviewed and isolated organisms were screened for bla KPC using PCR. Results: Of the first 75 patients enrolled in the CRaCKLe 2 study, 8 (10.7%) were found to harbor two distinct species of CRE. The mean age was 71.8 (SD of ± 7.1) years. Seven (87.5%) had been previously hospitalized within the last year, and all spent time in an ICU during this hospital stay. Two patients were colonized with CRE by the time of hospitalization; however the remainder had received an average of 5.2 (± 2.1) different antibiotics over a course of 22.9 (± 9.1) days of treatment prior to the isolation of a CRE. Bacteria were acquired from urine (seven isolates), the respiratory tract (seven isolates), and from abdominal fluid (two isolates), with both organisms found in a single site in five patients, and from separate sites in the remaining three patients. PCR of isolates identified bla KPC genes in both organisms in six patients; however, two of the patients harbored one organism with a bla KPC gene and one without. Conclusion: Hospitalized patients may develop multiple distinct CRE at the same or different sites, with potential risk factors including age, prior hospitalization, ICU stay, and exposure to multiple antibiotics over a prolonged course. Our data support co-infection occurring via (i) increased nosocomial exposure to CRE in the setting of repeated hospitalization and ICU admission, (ii) independent selective pressure due to heavy antibiotic exposure, as supported by the appearance of bla KPC and non- bla KPC species in the same host, or (iii) transfer of bla KPC -containing plasmids in the host environment, as suggested by the appearance of resistant species in those already infected with another CRE. Disclosures: All authors: No reported disclosures.